Penerapan Model Children’s Learning in Science Berbasis Kearifan Lokal pada Pembelajaran IPA Siswa Kelas IV SD Negeri 3 Srikaton - Tanti Meifisya; Asep Sukenda Egok; Armi Yuneti (Journal of Elementary School (JOES), 2020)
This research aims to find out the results of science study of grade IV students of Srikaton State 3 Srikaton District Musi Rawas after the study model of Children's Learning in Science based on local wisdom. This research method uses experimental research methods with pre-test and post-test group experiment designs. Sampling is taken from the population, considering that there is only one class, the total sampling is 23 students. The instrument used is a question of description that amounts to 8 questions. Data collection is taken with test techniques. The data is analyzed using the "z" test formula. Based on the hypothetical test results obtained zhitung = 3.35 and ztabel with a significant level of α = 0.05 in obtained ztabel = 1.64, then zhitung 3.35 > ztabel 1.64 which means Ho is rejected and Ha accepted. So it can be concluded that the results of science study of grade IV students of Srikaton State Elementary School after the completion of the children's learning in science model based on local wisdom are significantly complete. Keywords: Children's Learning in Science Learning Model, Learning Outcomes.